Search code examples
inputbooleanalgebrasimplification

Boolean Algebra simplification (3 inputs)


I may need your help with this quite simple thing: This -> abc' + ab'c + a'bc + abc can (I guess) be simplified to this -> ab+ac+bc.

But how in the world is this done with Boolean algebra?

I already reduced it to -> abc'+ab'c+bc by using the absorption rule on the last two terms [a'bc + abc]. But how can I reduce the rest of it to get the end result?


Solution

  • Before simplifying the expression I'll show you one nice trick that will be used later. For any two logical variables A and B the following holds:

    A + AB = A(B + 1) = A
    

    With this in mind let's simplify your expression:

    abc' + ab'c + a'bc + abc = ac(b + b') + abc' + a'bc = ac + abc' + a'bc
    

    We can expand ac in the following way using that 'trick' I mentioned before:

    ac = ac + abc = ac(b + 1) = ac
    

    Using this we get:

    ac + abc' + a'bc = 
    ac + abc + abc' + a'bc =
    ac + ab(c + c') + a'bc = 
    ac + ab + a'bc =
    ac + ab + abc + a'bc =
    ab + bc(a + a') + ac =
    ab + ac + bc
    

    Leading to the final expression you wanted to get in the first place.